Comprehension of Written Texts: Reconceptualizing 21st century challenges - Parodi Sweis, Giovanni; Moreno-de-León, Tomás; Julio , Cristobal (Íkala, Revista de Lenguaje y Cultura, 2020)
The rapid pace of technological developments at the beginning of the 21st century has posed tremendous challenges for researchers concerned with written texts comprehension from an academic and professional multiliteracy approach. It is now imminent to acknowledge the demands that reading comprehension implies not only for paper formats, but also for diverse electronic media, and diverse reading purposes. It is also vital to consider the comprehension of multiple texts and of eventually heterogeneous and highly multimodal genres. Nowadays, due to the immediate access and online availability of growing general and specialized information, the comprehension of such texts imposes incremental demands to human cognitive systems. This article seeks to address that complexity beginning with the conceptualization of the comprehension macroprocess, as it involves an eminently verbal single text, and continuing with the processing of multiple multimodal and multimedia texts, academic and professional genres, and the texts that characterize the XXI century, including the challenges that this represents to readers now and in the future.